If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + -6 = 9 + -2t Reorder the terms: -6 + 3t = 9 + -2t Solving -6 + 3t = 9 + -2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2t' to each side of the equation. -6 + 3t + 2t = 9 + -2t + 2t Combine like terms: 3t + 2t = 5t -6 + 5t = 9 + -2t + 2t Combine like terms: -2t + 2t = 0 -6 + 5t = 9 + 0 -6 + 5t = 9 Add '6' to each side of the equation. -6 + 6 + 5t = 9 + 6 Combine like terms: -6 + 6 = 0 0 + 5t = 9 + 6 5t = 9 + 6 Combine like terms: 9 + 6 = 15 5t = 15 Divide each side by '5'. t = 3 Simplifying t = 3
| 233-7x=29x+21 | | 3.4x+8.7=1.7x+18.9 | | 10x+10=20x+20 | | x^5-x^3+x+1=0 | | 3x+x+2=2x-4 | | 31-9(y+5)=7 | | x^3-96x^2+576x=0 | | -17-9=8x+17 | | 7y-9=33 | | 4x24= | | 5(2x-1)+16=8x+1 | | 3x+1=2x-1 | | -24=6a-15-15a | | 10-10x=75-45x | | 5x-4=-4+5x | | x^4-x^3+1=0 | | 5x=4(x+3) | | 5a-9=26 | | 1=14(2r+1) | | 14-6x=2x+66 | | 8x+29x-6= | | 1.4m-06(m-2)=2.4m | | 2x+40=12x-40 | | 5x-4=2x+6+x | | 37x=9x+4 | | 2(x-7)=10-4x | | 25x^2-15x-4=0 | | 12-6x=6x+34 | | 6x-10=46 | | 2+5+6rs= | | 2(y-6)-(y+2)=26 | | (x^2+16)(x^3-108)=0 |